2016
DOI: 10.1521/pedi_2015_29_193
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Single Features of Borderline Personality Disorder: Anger, Affective Instability, Impulsivity, and Chronic Emptiness in Psychiatric Outpatients

Abstract: Although dimensional models of borderline personality disorder (BPD) are consistent with findings showing that minimal levels of pathology are associated with substantial increases in psychosocial impairment, it is still unclear whether different individual BPD criteria are each clinically significant on their own. The current study uses semistructured interview data from 1,870 adults presenting for outpatient psychiatric treatment to investigate whether the BPD criteria of impulsivity, affective instability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 41 publications
4
63
1
Order By: Relevance
“…A recent study revealed that the number of below-threshold BPD features endorsed is significantly related to six different psychosocial morbidity outcomes, including psychiatric hospitalizations and suicidal ideation (Zimmerman, Chelminski, Young, Dalrymple, & Martinez, 2013). In fact, the presence of just one BPD symptom has been found to be significantly related to clinical impairment (Ellison, Rosenstein, Chelminski, Dalrymple, & Zimmerman, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the number of below-threshold BPD features endorsed is significantly related to six different psychosocial morbidity outcomes, including psychiatric hospitalizations and suicidal ideation (Zimmerman, Chelminski, Young, Dalrymple, & Martinez, 2013). In fact, the presence of just one BPD symptom has been found to be significantly related to clinical impairment (Ellison, Rosenstein, Chelminski, Dalrymple, & Zimmerman, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Research examining psychosocial impairment has produced mixed results, with studies variously identifying dysphoric mood, affect dysregulation, impulsivity, suicidal behaviour, identity disturbance and chronic emptiness . Recent efforts have focused on symptoms of identity disturbance and emptiness.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with borderline personality disorder (BPD) present with a clinically relevant heterogeneity [1] regarding severity of the disease [2] and specific features, such as anger [3], rejection sensitivity [4], personality organization [5], or depression [6]. This heterogeneity in core psychopathology has been associated with therapeutic outcome [7-9].…”
Section: Introductionmentioning
confidence: 99%